2019
DOI: 10.1590/1807-1929/agriambi.v23n3p167-174
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal fungi and auxin associated with microelements in the development of cuttings of Varronia leucocephala

Abstract: The plant Varronia leucocephala is widely used in Brazil for its therapeutic properties. However, a major problem for the seedlings is the low percentage of root formation. The objective of this study was to establish a rooting protocol for V. leucocephala cuttings, using phytoregulators and microelements associated with arbuscular mycorrhizal fungi. The auxin indole-3-butyric acid (IBA) concentration of 1500 mg L-1 showed the best rooting percentage, and it is proposed associating the microelements zinc and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
2
1
0
Order By: Relevance
“…Overall, AMF promoted adventitious root formation and rooting rate of tea cuttings ( Figures 2 and 4 ; Supplementary Figure 3 ), which was consistent with finding of previous studies in herbaceous ( Thanuja et al., 2002 ; Sohn et al., 2003 ; Fernades et al., 2019 ) and woody plants ( Han et al., 2013 ; Amri, 2015 ; Essahibi et al., 2017 ). Treatment of exogenous auxin shared similar results with AMF inoculation, both of which increased the rooting rate of cuttings of different tea plant varieties, especially in the ‘Longjingchangye’ variety which was relatively difficult to root according to our results ( Figure 3 and 4 ; Supplementary Figure 3 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Overall, AMF promoted adventitious root formation and rooting rate of tea cuttings ( Figures 2 and 4 ; Supplementary Figure 3 ), which was consistent with finding of previous studies in herbaceous ( Thanuja et al., 2002 ; Sohn et al., 2003 ; Fernades et al., 2019 ) and woody plants ( Han et al., 2013 ; Amri, 2015 ; Essahibi et al., 2017 ). Treatment of exogenous auxin shared similar results with AMF inoculation, both of which increased the rooting rate of cuttings of different tea plant varieties, especially in the ‘Longjingchangye’ variety which was relatively difficult to root according to our results ( Figure 3 and 4 ; Supplementary Figure 3 ).…”
Section: Discussionsupporting
confidence: 91%
“…Adventitious root (AR) formation is the most critical step in cutting propagation, and a good root system architecture is crucial to the survival rate and resistance of seedlings to various stresses after transplanting ( Chen et al., 2016 ). Previous studies have shown that arbuscular mycorrhizal fungus (AMF), which can form a symbiotic relationship with the roots of most terrestrial plants, has great potential to affect plant cutting propagation ( Ávila Díaz-Granados et al., 2009 ; Krishna et al., 2013 ; Essahibi et al., 2017 ; Fernades et al., 2019 ) and construction of root system architecture ( Chen et al., 2016 ), however, there are still few studies on the effect of AMF on the rooting of tea cuttings ( Liu and Lei, 1995 ; Gao et al., 2023 ), which mainly focused on the growth of tea seedlings in the later stage without covering the regulatory mechanism of adventitious root formation induced by AMF in the early stage. Therefore, in this paper, in order to decipher the relative mechanism, we divided the rooting state of tea cuttings into four stages for the first time ( Figure 1 ) : S0 (stage of non-rooting), S1 [stage of adventitious root (AR) protrusion], S2 (stage of AR formation) and S3 (stage of AR elongation).…”
Section: Discussionmentioning
confidence: 99%
“…The necrotic points visualized in the plants treated with NaCl may be related to ion accumulation, since excess ions result in morphological changes (smaller leaves and fewer leaves) and even cell death. However, it is worth mentioning that despite the evidence of oxidative stress, the plants had higher dry biomass content when inoculated with C. etunicatum in the most severe stress scenario, suggesting an attenuation of the effects of stress, which corroborates with the literature on the performance of this fungus in relation to better absorption of water and nutrients, better nutrition, greater contents of reserve substances, and greater vegetative development of plants when considering physiological mechanisms (SILVEIRA et al, 2002;FERNANDES et al, 2019).…”
Section: Souza Et Alsupporting
confidence: 85%
“…Therefore, exogenous IBA application assists in the plant-AMF symbiotic association. The symbiotic association with AMF promotes faster and higher plant growth through higher efficiency in the absorption and translocation of macro-and micronutrients (FERNANDES et al, 2019).…”
Section: Sapelli Et Almentioning
confidence: 99%